2015
DOI: 10.1155/2015/256534
|View full text |Cite
|
Sign up to set email alerts
|

Induced Second Trimester Abortion and Associated Factors in Amhara Region Referral Hospitals

Abstract: Background. Although the vast majority of abortions are performed in the first trimester, still 10–15% of terminations of pregnancies have taken place in the second trimester period globally. As compared to first trimester, second trimester abortions are disproportionately contribute for maternal morbidity and mortality especially in low-resource countries where access to safe second trimester abortion is limited. The main aim of this study was to assess the prevalence and associated factors of induced second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 19 publications
3
55
2
2
Order By: Relevance
“…In addition this study revealed females whose families live in rural were more likely to be knowledgeable than those whose families live in urban. This finding is opposite with findings from Amhara region referral hospitals in which place of residence affects the respondent's knowledge about safe abortion [20]. This may live from urban area [AOR = 1.56, 95% of CI: (1.03, 2.39)].…”
Section: Not Knowledgeablecontrasting
confidence: 68%
“…In addition this study revealed females whose families live in rural were more likely to be knowledgeable than those whose families live in urban. This finding is opposite with findings from Amhara region referral hospitals in which place of residence affects the respondent's knowledge about safe abortion [20]. This may live from urban area [AOR = 1.56, 95% of CI: (1.03, 2.39)].…”
Section: Not Knowledgeablecontrasting
confidence: 68%
“…During the study period, total of 171 clients underwent CAC service, out of which 79% received first trimester abortion service and 21% received second trimester abortion service. The incidence of induced second trimester abortion in our study is higher than the global incidence which constitutes only 10-15% 5 but is in line with study in Northwest Ethiopia that was 19.2% 6 and lower than that of India which was 25-30 percent. 7 Among the CAC clients, 33% were of age group 20-25 years and 28.65% were 26-30yrs which is explained by women's most fecund years while 5.84% were adolescence pregnancy which is similar to the study done in Tribhuvan University Teaching Hospital (TUTH), Nepal.…”
Section: Discussionsupporting
confidence: 90%
“…The experiences of women in Ethiopia who have undergone unsafe abortion remain largely under-researched. This is particularly the case for young, unmarried women, who constitute a significant proportion of the women who undergo unsafe abortion (Bonnen, Tuijje, & Rasch, 2014;Geleto & Markos, 2015;Mulat, Bayu, Mellie, & Alemu, 2015) and whose experiences are at the centre of the present discussion. Considering the high number of unmarried, young women who undergo unsafe abortion procedures, and as argued by Coast and Murray, it is of vital importance to investigate women's routes to clandestine and medically unsafe abortion more closely (Coast & Murray, 2016).…”
mentioning
confidence: 92%